2016
DOI: 10.1097/ccm.0000000000001572
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Trial of Thiamine as a Metabolic Resuscitator in Septic Shock

Abstract: Objective To determine if intravenous thiamine would reduce lactate in patients with septic shock. Design Randomized, double-blind, placebo-controlled trial. Setting Two US hospitals. Patients Adult patients with septic shock and elevated (> 3 mmol/L) lactate between 2010 and 2014. Interventions Thiamine 200 mg or matching placebo twice daily for 7 days or until hospital discharge. Measurements and Main Results The primary outcome was lactate levels 24 hours after the first study dose. Of 715 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
264
5
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(284 citation statements)
references
References 38 publications
5
264
5
10
Order By: Relevance
“…In a randomized controlled trial by Donnino et al, thiamine administration did not improve lactate levels or clinical outcomes in adults with septic shock the overall group. However, it is noteworthy that in those with baseline TD, patients in the thiamine-supplemented group had lower serum lactate at 24 h and in-hospital mortality (21). Further studies are necessary to determine which groups of patients are expected to benefit from this intervention.…”
mentioning
confidence: 99%
“…In a randomized controlled trial by Donnino et al, thiamine administration did not improve lactate levels or clinical outcomes in adults with septic shock the overall group. However, it is noteworthy that in those with baseline TD, patients in the thiamine-supplemented group had lower serum lactate at 24 h and in-hospital mortality (21). Further studies are necessary to determine which groups of patients are expected to benefit from this intervention.…”
mentioning
confidence: 99%
“…Еюнальный доступ не снижает объем доставки энергии, не снижает частоту ВАП, но частота малых гастроинтестинальных кровотечений выше, чем при гастральном доступе. Следовательно, рутинное применение не рекомендуется [24].…”
Section: застой в печени и спланхническом регионеunclassified
“…New data indicate that thiamine deficiency occurs in up to 35% of septic shock patients [53]. A recent randomized, double-blind, controlled trial showed that administration of 200 mg thiamine to patients with septic shock did not improve lactate levels or other outcomes overall [53].…”
Section: Management Goals For Nutrition In Sepsis (See Table 1a mentioning
confidence: 99%